THE APPLICATION OF HYBRID PIGMENTS IN THE FORMATION OF A POLYMER-MINERAL COATING FOR LEATHER FINISHING - BONDARYEVA Аnna; MOKROUSOVA Оlena (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper is focused to the study of the physical and mechanical properties of a polymer-mineral coating based on hybrid pigments for leather finishing. The aim of this research is to study the effect of hybrid pigments based on montmorillonite on the formation of a polymer-mineral coating for leather finishing. Hybrid pigments obtained by complex modification of native montmorillonite with sodium carbonate and basic chromium (III) sulfate with further subsequent adsorption of anionic dyes on the cationic surface of the mineral particles were used for this research. A ready-made mixture of various structures film-formers, intended for the finishing of facial and polished leather was used as a film-former. For the leather finishing, coating paints were prepared in the form of polymer-mineral compositions by mixing hybrid pigments with a film-forming agent in the ratio, wt. part 1: 5. In this study it was calculated that montmorillonite consumption at the level of 1.5-2.0% in terms of the mass of montmorillonite from the mass of dry polymer residue was optimal for obtaining high physical and mechanical properties of polymer films for finishing leather. A mechanism for structuring the polymer matrix with a hybrid pigment was proposed. According to this mechanism the highly developed sorption surface of montmorillonite provided adsorption of the polymer and stabilized its structure with the formation of a mixed polymer-mineral composite. It was shown that the use of montmorillonite in the composition of hybrid pigment allowed to adjust the physical and mechanical properties of the polymer-mineral composition for leather finishing, provided an increase in strength and regulated the level of elasticity of the covering film, which ensured an increase in the operational properties of the leather coating.